Answers

  • Brainly User
2015-11-13T22:46:50+08:00
Let the first integer be x
Second integer be x + 2
Product of the two integers = 624

Equation:
(x) (x + 2) = 624
x² + 2x = 624

Transform to quadratic equation ax² + bx +c = 0
x² + 2x - 624 = 0

Solve by factoring or quadratic formula.

By factoring:
x² + 2x - 624 = 0
(x - 24) (x + 26) = 0
x - 24 = 0                  x + 26 = 0
x = 24    

Choose the positive root, x = 24.

First even integer: x    ⇒   24
Second integer: x + 2 = 24 + 2     ⇒  26

The two consecutive even integers are 24 and 26.

Check:
(24) (26) = 624
624 = 624


1 5 1